The Excavations at Nimrud (Kalḫu) 1956 - Mallowan, M. E. L.
Progress and Scope of the 1956 Excavations — Ezida: Temple of Nabu — Ezida: Stratigraphy Inscriptions, Notes on Small Finds. Hellenistic Occupation — The Ninurta Temple — The Town Wall Palace of Aššur-bani-pal.